2015
DOI: 10.1128/jvi.03651-14
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Virion-Associated σ1 Fibers on Oncolytic Reovirus Variants Promotes Adaptation toward Tumorigenic Cells

Abstract: Wild-type mammalian orthoreovirus serotype 3 Dearing (T3wt) is nonpathogenic in humans but preferentially infects and kills cancer cells in culture and demonstrates promising antitumor activity in vivo. Using forward genetics, we previously isolated two variants of reovirus, T3v1 and T3v2, with increased infectivity toward a panel of cancer cell lines and improved in vivo oncolysis in a murine melanoma model relative to that of T3wt. Our current study explored how mutations in T3v1 and T3v2 promote infectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 69 publications
2
26
0
Order By: Relevance
“…For example, many reovirus protein functions have been characterized by comparing phenotypes among natural reovirus variants, reovirus genome reassortants, and laboratory derived reovirus mutants10111213141516171819. In conjunction with reverse genetics approaches for these viruses202122232425, it is now possible to design copious virus mutants, purify them in-slurry, and make rapid comparisons of virus proteins, virion structure, and virus replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many reovirus protein functions have been characterized by comparing phenotypes among natural reovirus variants, reovirus genome reassortants, and laboratory derived reovirus mutants10111213141516171819. In conjunction with reverse genetics approaches for these viruses202122232425, it is now possible to design copious virus mutants, purify them in-slurry, and make rapid comparisons of virus proteins, virion structure, and virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both reovirus and adenovirus are heavily pursued as oncolytic therapies. We and others have demonstrated that reovirus mutants exhibit differences in their oncolytic activities, and that second-generation reovirus variants may possess improved oncolytic potency17192627. We have found the Capto Core 700 slurry method to be extremely useful for purifying and comparing various natural isolates (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Encapsidation and folding of 1 coiled-coil-to-body transition mutants. Reovirus variants and mutants with polymorphisms in the 1 sequence encapsidate different amounts of 1 fibers (31,32). Using quantitative immunoblotting, we found that the mutant viruses encapsidate approximately 50% (rsT3SA ϩ 1 R161A and rsT3SA ϩ 1 N182A) or 30% (rsT1L 1 R161A,N182A) of the amount of 1 encapsidated by the parental rsT3SA ϩ virus (Fig.…”
Section: Features Of the Reovirus 1 Tailmentioning
confidence: 91%
“…The 1 proteins of T3D TD and T3D KC differ from T3D PL at 2 positions ( Figure 1I). We consider it likely 271 that the alanine-to-valine change at position 22 is responsible for decreased levels of σ1 on T3D TD and T3D KC 272 virions , as we and others previously found that mutations in the σ1 anchor domain (amino acids 1-27) affect 273 incorporation of σ1 trimers into the λ2 vertex (Bokiej et al, 2012;Mohamed et al, 2015;Nygaard et al, 2013). 274…”
mentioning
confidence: 85%